Cardiovascular risk associated with glucagon-like peptide-1 receptor agonists versus other conventional glucose-lowering drugs in patients with type-2 diabetes: protocol for a nationwide observational comparative study in routine care - François Schiele; Mikael Mazighi; Nicolas Danchin; Igor Sibon; Gilles Lemesle; Kamel Mohammedi; Laurent Fauchier; Bruno Detournay; Alexandre Caron; Corinne Emery; Camille Nevoret; Lucile Vigié; et al. (BMJ Open)
Introduction Several cardiovascular outcome trials have been conducted to assess the cardiovascular safety and efficacy of glucagon-like peptide-1 receptor agonists (GLP1-RAs) on cardiorenal outcomes in patients with type-2 diabetes (T2D). However, the strict requirements of randomised controlled trials to avoid most confounding factors are at the expense of external validity. Using national real-world data, we aimed to evaluate the effectiveness of GLP-1RAs in association with metformin especially on cardiovascular events, hospitalisation for heart failure and all-cause death in comparison with other diabetes treatment schemes using dipeptidyl peptidase IV inhibitors, sulfonylureas/glinides or insulin also associated with metformin. Sodium-glucose transport protein 2 inhibitors (SGLT-2i) will be excluded as comparators, as this class of oral hypoglycaemic agents just started in 2020 to be marketed in France.Methods and analysis The Système National des Données de Santé is a comprehensive nationwide administrative healthcare database in France that covers approximately 67 million people.Several cohorts of adult patients with T2D initiating any GLP1-RA in dual or triple therapies, as recommended by the French Health authorities, will be identified in this database over the period 2016–2021. These cohorts will be defined by the combination of glucose-lowering drugs prescribed simultaneously with GLP1-RA and diabetes treatment received over a 6-month period before GLP1-RA initiation. They will be first matched with T2D controls (1:3 ratio) based on the year of drug initiation and treatment regimens before and simultaneously with GLP1-RA in the different selected cohorts. Comparative analyses will be conducted versus these control groups, adjusting for cardiovascular event history and a propensity score considering age, sex, area of residence, deprivation index, comorbidities, duration of diabetes, use of lipid-lowering drugs, anticoagulants, antiplatelet therapies and blood pressure-lowering therapies. Comparative analyses will be conducted versus these control groups, using a high-dimensional propensity scores method and fixed baseline characteristics. Treatment effects on the different outcomes measured will be estimated for each GLP1-RA group, through HR and their corresponding CIs (95% CI) using Cox regressions and/or competitive risk regressions when necessary.Ethics and dissemination The study has been approved by an independent ethics committee (Comité éthique et scientifique pour les recherches, les études et les évaluations dans le domaine de la santé, Paris, France; reference: 8699786, dated 2 June 2022) and has been registered with the French National Data Protection Commission (Commission Nationale de l'Informatique et des Libertés, Paris, France; reference: 922161, dated 26 June 2022). The findings of this study will be published in peer-reviewed scientific journals and presented at international conferences.Trial registration number F20220803152803.